Biomechanical Comparison of Vertebroplasty, Kyphoplasty, Vertebrae Stent for Osteoporotic Vertebral Compression Fractures—A Finite Element Analysis - Jen-Chung Liao; Michael Jian-Wen Chen; Tung-Yi Lin; Weng-Pin Chen (Applied Sciences, 2021)
Vertebroplasty (VP), balloon kyphoplasty (BKP), and vertebral stent (VS) are usually used for treating osteoporotic compression fractures. However, these procedures may pose risks of secondary adjacent level fractures. This study simulates finite element models of osteoporotic compression fractures treated with VP, BKP, and VS Vertebral resection method was used to simulate vertebra fracture with Young’s modulus set at 70 MPa to replicate osteoporosis. A follower load of (1175 N for flexion, and 500 N for all others) was applied in between vertebral bodies to simulate the muscle force. Moment loadings of 7.5 N-m in flexion, extension, lateral bending, axial rotation were applied respectively. The VS model had the highest von Mises stresses on the bone cement under all different loading conditions (flexion/5.91 MPa; extension/3.74 MPa; lateral bending/3.12 MPa; axial rotation/3.54 MPa). The stress distribution and maximum von Mises stresses of the adjacent segments, T11 inferior endplate and L1 superior endplate, showed no significant difference among three surgical models. The postoperative T12 stiffness for VP, BKP, and VS are 2898.48 N/mm, 4123.18 N/mm, and 4690.34 N/mm, respectively. The VS model led to superior surgical vertebra stiffness without significantly increasing the risks of adjacent fracture.